2021
DOI: 10.1259/bjr.20210670
|View full text |Cite
|
Sign up to set email alerts
|

Proton therapy for prostate cancer: current state and future perspectives

Abstract: Objective: Localized prostate cancer can be treated with several radiotherapeutic approaches. Proton therapy (PT) can precisely target tumors, thus sparing normal tissues and reducing side-effects without sacrificing cancer control. However, PT is a costly treatment compared with conventional photon radiotherapy, which may undermine its overall efficacy. In this review, we summarize current data on the dosimetric rationale, clinical benefits, and cost of PT for prostate cancer. Methods: An extensive literature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 101 publications
0
7
0
Order By: Relevance
“…As prostate cancer is the most common solid cancer in men, 1 it accounts for a substantial portion of proton beam therapy (PBT) in the United States. 2,3 Much of this adoption is being driven by the theoretical benefits of proton beam radiation over intensity-modulated radiation therapy (IMRT) because of physical advantages in radiation dose deposition that could potentially translate to a reduction in treatment-related genitourinary (GU) and GI toxicity for men undergoing prostate radiation. 3 However, despite these theoretical benefits, early evaluation of the comparative effectiveness of proton and photon beam treatments using Medicare claims and nonrandomized patient-reported outcomes demonstrated that there were no significant benefits to PBT compared with IMRT.…”
Section: Introductionmentioning
confidence: 99%
“…As prostate cancer is the most common solid cancer in men, 1 it accounts for a substantial portion of proton beam therapy (PBT) in the United States. 2,3 Much of this adoption is being driven by the theoretical benefits of proton beam radiation over intensity-modulated radiation therapy (IMRT) because of physical advantages in radiation dose deposition that could potentially translate to a reduction in treatment-related genitourinary (GU) and GI toxicity for men undergoing prostate radiation. 3 However, despite these theoretical benefits, early evaluation of the comparative effectiveness of proton and photon beam treatments using Medicare claims and nonrandomized patient-reported outcomes demonstrated that there were no significant benefits to PBT compared with IMRT.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, PArc has demonstrated great potential to improve treatment quality for prostate cancer over bilateral robustly optimized proton pencil beam scanning, while being deliverable within a clinically acceptable time [21]. Specifically, PArc could significantly spare the femoral heads compared to the conventional PT method [21,22]. Although PArc is a new modality, it is gaining increased interest and is an active area of research and the clinical implementation is ongoing [11,[23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…This allows for the effective sparing of surrounding healthy tissue and organs at risk and thus reducing treatment toxicity. Proton therapy is routinely used for the treatment of various tumor sites [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ] and is a dynamically developing form of radiotherapy [ 20 ].…”
Section: Introductionmentioning
confidence: 99%